2009
DOI: 10.1038/bmt.2009.210
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole provides effective prophylaxis for invasive fungal infection in patients receiving glucocorticoid therapy for GVHD

Abstract: Patients on systemic glucocorticoids for graft-versus-host disease (GVHD) after hematopoietic cell transplant are susceptible to invasive fungal infections (IFI), which greatly contribute to morbidity and mortality. We evaluated the efficacy of prophylactic treatment options (voriconazole versus fluconazole or itraconazole) for IFI by performing a retrospective review of patients on glucocorticoids for GVHD given voriconazole (n = 97), fluconazole (n = 36), or itraconazole (n = 36). IFI developed in 7/72 (10%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…However, patients with GvHD involving the gastrointestinal tract were not well represented in this study, as they may not be able to take oral agents, and posaconazole is available only in oral suspension. Another retrospective study among patients receiving systemic glucocorticoids for GvHD after HSCT showed that voriconazole was more effective than fluconazole/itraconazole in preventing IC [42].…”
Section: Prophylaxismentioning
confidence: 98%
“…However, patients with GvHD involving the gastrointestinal tract were not well represented in this study, as they may not be able to take oral agents, and posaconazole is available only in oral suspension. Another retrospective study among patients receiving systemic glucocorticoids for GvHD after HSCT showed that voriconazole was more effective than fluconazole/itraconazole in preventing IC [42].…”
Section: Prophylaxismentioning
confidence: 98%
“…Recently, one centre has reviewed their experience with voriconazole administered either orally or intravenously to allogeneic HSCT recipients receiving at least 1 mg/kg/d of prednisolone for GVHD and reported only two Candida spp infections in 97 patients (Gergis et al , 2009). GVHD was initially graded as grade 3–4 in 31% of these patients.…”
Section: Evidence For Antifungal Prophylaxis: Randomized Studiesmentioning
confidence: 99%
“…Posttransplant hypomethylation is an evolving concept; it does not seem to affect chimerism or GVHD (compared with DLI). The advent of low-intensity conditioning, highresolution HLA typing, and improved supportive care have resulted in a marked decrease in NRM [50,51]. Nevertheless, relapse rates are still high, at a rate of 25% to 50%.…”
Section: Discussionmentioning
confidence: 97%